Gene expression in blood from an individual with β‐thalassemia: An RNA sequence analysis. Issue 7 (27th May 2019) - Taghavifar, Forough; Hamid, Mohammad; Shariati, Gholamreza
Abstract: Background: Transcriptome profiling in individuals affected with β‐thalassemia, especially in individuals who carry novel mutations in the HBB, may improve our understanding of the heterogeneity and molecular mechanisms of the disease. Methods: Members of a family with a daughter affected with thalassemia intermedia, although her mother was not clinically affected, were examined. We also characterized genome‐wide gene expression in the family using real‐time quantitative polymerase chain reaction and high‐throughput RNA‐sequencing mRNA expression profiling of blood. Results: We described the downregulation of the β‐globin gene in β‐thalassemia by RNA‐sequencing analysis using a sample from an affected individual and her mother, who have a novel mutation in the HBB that creates a cryptic donor splice site. The daughter has a typical β‐thalassemia allele as well, and an unexpectedly severe phenotype. The differentially expressed genes are enriched in pathways that are directly or indirectly related to β‐thalassemia such as hemopoiesis, heme biosynthesis, response to oxidative stress, inflammatory responses, immune responses, control of circadian rhythm, apoptosis, and other cellular activities. Conclusion: We compare our findings with published results of RNA‐sequencing analysis of sickle cell disease and erythroblasts from a KLF1‐null neonate with hydrops fetalis, and recognize similarities and differences in their transcriptional expression patterns. Abstract : Transcriptome profiling in individuals affected with β‐thalassemia, especially in individuals who carry novel mutations in the HBB, may improve our understanding of the heterogeneity and molecular mechanisms of the disease.